Nano-Lipids Based on Ginger Oil and Lecithin as a Potential Drug Delivery System - Hung Quach; Tuong-Vi Le; Thanh-Thuy Nguyen; Phuong Nguyen; Cuu Khoa Nguyen; Le Hang Dang (MDPI AG, 2022)
Lipid nanoparticles based on lecithin are an interesting part of drug delivery systems. However, the stability of lecithin nano-lipids is problematic due to the degradation of lecithin, causing a decrease in pH. In this study, the modification of the conventional nano-lipid-based soybean lecithin was demonstrated. Ginger-oil-derived Zingiber officinale was used along with lecithin, cholesterol and span 80 to fabricate nano-lipids (GL nano-lipids) using a thin-film method. TEM and a confocal microscope were used to elucidate GL nano-lipids' liposome-like morphology. The average size of the resultant nano-lipid was 249.1 nm with monodistribution (PDI = 0.021). The ζ potential of GL nano-lipids was negative, similarly to as-prepared nano-lipid-based lecithin. GL nano-lipid were highly stable over 60 days of storage at room temperature in terms of size and ζ potential. A shift in pH value from alkaline to acid was detected in lecithin nano-lipids, while with the incorporation of ginger oil, the pH value of nano-lipid dispersion was around 7.0. Furthermore, due to the richness of shogaol-6 and other active compounds in ginger oil, the GL nano-lipid was endowed with intrinsic antibacterial activity. In addition, the sulforhodamine B (SRB) assay and live/dead imaging revealed the excellent biocompatibility of GL nano-lipids. Notably, GL nano-lipids were capable of carrying hydrophobic compounds such as curcumin and performed a pH-dependent release profile. A subsequent characterization showed their suitable potential for drug delivery systems.